2020
DOI: 10.1186/s13006-020-00320-w
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial barriers and enablers of exclusive breastfeeding: lived experiences of mothers in low-income townships, North West Province, South Africa

Abstract: Background: Despite national efforts to promote exclusive breastfeeding (EBF), South Africa's EBF rate is only 32 %. The aim of this study was to examine the rate of EBF discontinuation and the lived experiences of breastfeeding mothers at postnatal time points 3-14 days, 4-8 weeks, 10-14 weeks and 20-24 weeks. Methods: This community-based mixed-methods study collected data within a prospective cohort study on sociodemographics, the Edinburgh Postnatal Depression Scale (EPDS) and the Breastfeeding Self-Effica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
2
18
2
4
Order By: Relevance
“…Other potential challenges could be the lack of sufficient breastfeeding knowledge among healthcare providers and their key role in encouraging lactating mothers [ 72 ]. Inadequate breastfeeding practices and premature weaning may also be due to the lack of designated maternity facilities such as lactation rooms in shopping malls, airports, and the workplace, lack of community or home support to the breastfeeding mother, high rates of prelacteal feeding, and the growth of infant formula milk companies in the market [ 37 , 72 , 77 , 78 , 79 , 80 ]. In terms of complementary feeding, although most infants were introduced to solid, semi-solid, or soft foods as per the WHO recommendations [ 15 ], less than half of those aged 6–23 months received a minimum acceptable diet and minimum diet diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential challenges could be the lack of sufficient breastfeeding knowledge among healthcare providers and their key role in encouraging lactating mothers [ 72 ]. Inadequate breastfeeding practices and premature weaning may also be due to the lack of designated maternity facilities such as lactation rooms in shopping malls, airports, and the workplace, lack of community or home support to the breastfeeding mother, high rates of prelacteal feeding, and the growth of infant formula milk companies in the market [ 37 , 72 , 77 , 78 , 79 , 80 ]. In terms of complementary feeding, although most infants were introduced to solid, semi-solid, or soft foods as per the WHO recommendations [ 15 ], less than half of those aged 6–23 months received a minimum acceptable diet and minimum diet diversity.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 Canadian study postulated that household food insecurity could be a predictor of breastfeeding initiation due to concerns on the cost of alternate feeding, but concerns over their own food and nutrient intake and the quality or quantity of breastmilk they produced may lead some mothers to introduce formula milk [ 28 ]. Reducing hunger in mothers by improving household food security and improving breastfeeding self-efficacy in mothers could lead to higher rates of exclusive breastfeeding [ 25 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is likely to increase stress levels in women. The stress that mothers from low-income households in South Africa experience could include concerns about their breastmilk supply, their access to food, having regular meals, and relationship difficulties in the home [ 29 ]. Women, in particular, face an increased care burden due to COVID-19, and this further increases the stress on them [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in various countries have reported the prevalence of postpartum depression between 8.6% and 44.8%. [4][5][6][7] Studies in Turkey reported this prevalence to be 14.6% to 27.7%. [8][9][10] It is reported that biological, psychological and sociocultural factors are effective in the etiology of postpartum depression.…”
Section: Introductionmentioning
confidence: 99%